Integrated Microfibre Device for Refractive Index and Temperature Sensing - Lim, Kok Sing; Aryanfar, Iman; Chong, Wu Yi; Cheong, Yew Ken; Harun, Sulaiman Wadi; Ahmad, Harith (MDPI, 2012)
A microfibre device integrating a microfibre knot resonator in a Sagnac loop reflector is proposed for refractive index and temperature sensing. The reflective configuration of this optical structure offers the advantages of simple fabrication and ease of sensing. To achieve a balance between responsiveness and robustness, the entire microfibre structure is embedded in low index Teflon, except for the 0.5-2 mm diameter microfibre knot resonator sensing region. The proposed sensor has exhibited a linear spectral response with temperature and refractive index. A small change in free spectral range is observed when the microfibre device experiences a large refractive index change in the surrounding medium. The change is found to be in agreement with calculated results based on dispersion relationships.